Teori Sistem Ekololgi Bronfenbrenner dan Implementasinya Dalam Model Pendidikan Integratif - Ni’mah, Azkia Faiqotun; Mawardi, Kholid (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2026)
Education is the core foundation of national development, necessitating a holistic quality reform. Efforts to improve human resources are insufficient if solely centered on formal institutions; they require a synergistic educational ecosystem involving schools, families, and communities. This research addresses the fragmentation of previous studies by offering a comprehensive analysis of an integrated education model. Specifically, it focuses on the interconnectedness, synergy, and coordination among various environments (Microsystem and Mesosystem) that influence child development, and presents a synthesis between formal-informal-nonformal education with character reinforcement based on Islamic values (Akhlakul Karimah). This study employs a qualitative library research method with data collection techniques utilizing documentation from books, articles, and journals. The data analysis technique is content analysis combined with a thematic-comparative approach to identify patterns and differences in character education implementation. The results demonstrate that the Bronfenbrenner’s Ecological Theory framework (Microsystem, Mesosystem, Exosystem, Macrosystem, Chronosystem) is an essential analytical tool for mapping multi-stakeholder coordination dynamics. The success of the Integrated Education Model critically depends on the consistency and synergy of values received by the child across different systems. The three main factors determining parenting behavior (Child Factor, Environmental Factor, and Parent's Individual Self Factor) within the Family Microsystem are crucial. Furthermore, the development of Akhlakul Karimah must be systemic and holistic, involving the three national pillars (schools, families, and communities), consistent with Bronfenbrenner's theory. Weak cross-system coordination (a weak Mesosystem) often creates a confusing disparity of values for students. Therefore, a strong collective commitment is needed to reinforce the communication and collaboration network among all ecological elements for the realization of holistic character education.